Epistemology of Ta'dib in Islamic Education(Critical Analysis to Prevent Bullying and Empowering Students’ Ethics) - Shobrun Jamil; Dimas Indianto S; Faizah Nur Atika; Amroeni (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Within the context of Islamic education, bullying reflects a crisis of adab and the failure to internalize educational values oriented toward the formation of morally upright individuals. This study explores the epistemology of ta’dib in Islamic education as a foundational framework for preventing bullying and strengthening students’ ethical development. Rooted in the intellectual tradition of classical Muslim scholars such as Syed Muhammad Naquib al-Attas and Al-Ghazali, the concept of ta’dib emphasizes the integration of knowledge (‘ilm), proper action (‘amal), and moral discipline (adab) as a unified educational paradigm. Using a critical-analytical approach, this research examines how the neglect of adab in contemporary educational practices contributes to moral disorientation and behavioral problems, including bullying. The study argues that bullying reflects an epistemological crisis—where knowledge is detached from ethical responsibility. The findings suggest that implementing a ta’dib-oriented framework requires integrating moral exemplarity, spiritual consciousness, and holistic curriculum design. Such an approach not only addresses bullying preventively but also empowers students to internalize ethical values as part of their identity. Ultimately, the epistemology of ta’dib offers a transformative paradigm for Islamic education that harmonizes intellectual growth with moral refinement, contributing to the formation of ethically responsible individuals and compassionate learning communities. Therefore, the epistemology of ta’dib offers a holistic framework for reconstructing Islamic education to address and prevent bullying by emphasizing moral cultivation, the integration of knowledge and ethics, and the development of a balanced human character encompassing intellectual, spiritual, and moral dimensions.